MARIA MONTESSORI: PEACE EDUCATION THROUGH DISCIPLINE - Peerzada, Najmah; Bashir, Nusrat (International Journal of Psychosocial Rehabilitation, 2019)
Maria Montessori, one of the most distinguished educator, philosopher, practitioner and thinker–renowned for her contributions to early childhood education. The main objective of the present study was to examine the concept of peace education through discipline. Montessori Peace Education is the foundation of the Montessori Method, which is a world changing technique that teaches children to be peaceful and positive members of a developing society. She also argued that the foundation of peace can be established through teaching the children. She emphasized that, it is feasible if children are consciously taught global citizenship, respect for diversity, and personal responsibility, which will provide them with the fortitude to refuse to allow their leaders to engage in conflict. She believed that ignoring the spiritual and moral education of children increases the likelihood of war. Both historical and philosophical methods have been used and primary as well as secondary sources have been employed for the collection of data. The study revealed that educationists and philosophers should develop moral laws and dignity among individuals. In her educational thought Montessori, stressed especially on the importance of discipline. She believed that the main tasks of education are disciplined thinking and imparting moral values among the students. In the present study, an attempt has been made to present an overview of Montessori peace education through discipline and analysing the data related to the theme.